Three new species of the freshwater snail genus Tylomelania (Caenogastropoda: Pachychilidae) from the Malili lake system, Sulawesi, Indonesia - Von Rintelen, Thomas; Glaubrecht, Matthias (Zootaxa, 2008)
The ancient Malili lake system on the Indonesian island Sulawesi hosts a large species flock of the viviparous freshwater gastropod Tylomelania. Molecular and morphological data have previously shown that this species flock resulted from three independent lake colonizations and subsequent adaptive radiations. In a recent taxonomic revision of these radiations 25 species have been recognized. Here we describe three new species from the system found during new sampling campaigns. Despite their highly distinct shell morphology, these species were previously overlooked because of their very restricted distribution range and, in one case, the very small size. Of these new species, two are endemic to a section of the Larona River, which drains the entire lake system, while the third species has only been found at one locality in central Lake Mahalona. The discovery of these species can contribute significantly to our understanding of evolution in the entire species flock, as two of the species form a basal branch of an entire clade and all show a high degree of habitat specialization. The local endemism of the Larona River species in particular makes them highly vulnerable to extinction caused by habitat destruction.